2010
DOI: 10.1364/oe.18.003672
|View full text |Cite
|
Sign up to set email alerts
|

Design of plasmonic photonic crystal resonant cavities for polarization sensitive infrared photodetectors

Abstract: Abstract:We design a polarization-sensitive resonator for use in midinfrared photodetectors, utilizing a photonic crystal cavity and a single or double-metal plasmonic waveguide to achieve enhanced detector efficiency due to superior optical confinement within the active region. As the cavity is highly frequency and polarization-sensitive, this resonator structure could be used in chip-based infrared spectrometers and cameras that can distinguish among different materials and temperatures to a high degree of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…Rosenberg et al showed that a metal-coated dots-in-a-well (DWELL) photonic crystal cavity can be designed to achieve significant free-space coupling of normal-incident light. 231 Additionally, Boriskina et al show that the large confinement of high-Q cavities could be combined with the superior light concentrating properties of nanoantennas to create optoplasmonic superlenses for low-loss energy transfer within optical circuits. 232 The proposed superlens is composed of a polystyrene microsphere sandwiched between two gold nanodimer antennas, creating a device that is well suited for frequency-sensitive enhancement and switching of light at the nanoscale.…”
Section: Recent Applications Of High-q Optical Sensorsmentioning
confidence: 99%
“…Rosenberg et al showed that a metal-coated dots-in-a-well (DWELL) photonic crystal cavity can be designed to achieve significant free-space coupling of normal-incident light. 231 Additionally, Boriskina et al show that the large confinement of high-Q cavities could be combined with the superior light concentrating properties of nanoantennas to create optoplasmonic superlenses for low-loss energy transfer within optical circuits. 232 The proposed superlens is composed of a polystyrene microsphere sandwiched between two gold nanodimer antennas, creating a device that is well suited for frequency-sensitive enhancement and switching of light at the nanoscale.…”
Section: Recent Applications Of High-q Optical Sensorsmentioning
confidence: 99%
“…The electromagnetic field profile of the SP structure was modeled using both a finite integration technique (CST Microwave Studio) 23 and a rigorous coupled wave analysis (RCWA) 24,25 . The refractive index of the material (n eff ) was taken to be the effective index of the first order resonance of SP modes (~ λ 1,0 /p) and the Drude model for the gold dielectric function at frequencies of interest is described by a plasma frequency p = 9.02 eV and a scattering frequency ω c = 0.027 eV [26][27] .…”
Section: Epitaxial Growth and Fabricationmentioning
confidence: 99%
“…From the last decade, due to the exotic properties of metamaterials at subwavelength scale they are in continuous use for the performance improvement of microwave absorbers [4]. The ultra-thin thickness and nearly unity absorbance property of a metamaterial based absorber make it a useful candidate from microwave to optical frequencies in many potential applications such as cloaking [5], antennas [6], radar imaging [7], thermal emission [8,9] photodetector [10], solar cells [11], etc. Metamaterial absorbers are so designed that incident electromagnetic energy on the structure manipulate its effective permittivity and permeability in such a way that input impedance of the structure become equals to the free space impedance and minimizes the reflection from it.…”
Section: Introductionmentioning
confidence: 99%